(Un)configurable masculinities and gender dynamics in men's eyes: "Mixed" couples of Filipino migrants in Belgium and the Netherlands. (March 2021) - Fresnoza-Flot, Asuncion
Studies on "mixed" couples focus mainly on women's perspectives, which results in the neglect of the viewpoints of men. Addressing this empirical gap, this research note investigates the case of Belgian and Dutch men in (former) relationship with Filipino women, and Filipino men (currently or previously) married to Belgian/Dutch women. Ethnographic data analysis unveils the importance of the traditional division of household chores to these men. Belgian and Dutch informants maintain a gendered division of labor in their respective households, whereas Filipino informants, whose Belgian/Dutch spouses pursue gender equality, adopt various strategies to regain their masculine self.